The Taxation of silver and copper in Poland - Drozdowski, Edgar (Издательский дом ВГУ, 2014)
The aim of this article is to present the new legislation in force regarding statutory charges levied on silver and copper, and to conduct a brief evaluation of the new regulations. The article comprises two elements: the description of the existing fi scal burdens levied on copper and silver on the basis of the Law on Geological Exploration and Mining of 9 June 2011, and the description of the new, parallel statutory charges introduced by the Law on taxation of extraction of certain minerals of 2 March 2012. The author of the article assesses the introduction of the new tax as a step in the right direction for several reasons. Firstly, the state has fi nally started collecting substantial resource rent. Secondly, constructing the tax as an output-based royalty appears to be rational and transparent. Lastly, the construction of a new tax takes into consideration both economic upturns and downturns. As a result, the new tax together with the previous fi scal burdens form a coherent system that «taxes» every aspect of mining business activity regarding copper and silver (corporate income tax, the tax on the extraction of certain minerals and royalty for the mineral exploited).
Keywords: taxation of silver and copper; Poland